Optical sensing of phenylalanine in urine via extraction with magnetic molecularly imprinted poly(ethylene-co-vinyl alcohol) nanoparticles. (10th July 2015) - Hsu, Chung-Yi; Lee, Mei-Hwa; Thomas, James L; Shih, Ching-Ping; Hung, Tzu-Lin; Whang, Thou-Jen; Lin, Hung-Yin
Abstract: Incorporation of superparamagnetic nanoparticles into molecularly imprinted polymers (MIPs) is useful for both bioseparations and for concentration and sensing of biomedically relevant target molecules in physiological fluids, through the application of a magnetic field. In this study, we combined the separation and concentration of a target (phenylalanine) in urine, using magnetic molecularly imprinted polymeric composite nanoparticles, with optical sensing, to improve assay sensitivity. This target is important as a catecholamine precursor, and as an important amino acid constituent of proteins. Poly(ethylene-co-vinyl alcohol)s were imprinted with target molecules, and showed a high imprinting effectiveness (target binding compared with binding to non-imprinted polymer particles.) Fluorescence spectrophotometry was used to measure binding of the target, and also binding of possible interfering compounds. These measurements suggest that functional groups on phenylalanine dominate the selectivity of the synthesized MIPs. Finally, the composite nanoparticles were used to separate and sense the target molecule in urine by Raman scattering microscopy.